INTERPRETASI STRUKTUR BAWAH PERMUKAAN DI MUARA SUNGAI PROGO MENGGUNAKAN METODE MAGNETIK - Dewi Andri; Muhammad Irham; Udi Harmoko (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Progo fault is one of the active faults located in the south of Yogyakarta. Progo fault is suspected that located in Progo River estuary area, Banaran, DIY. However, studies are still needed to support the scientific basis of the position and the type of fault in Progo River estuary. Magnetic survey has been carried out in DIY Progo River estuary to determine the subsurface structure in the area. Data needed in the processing of magnetic data is a magnetic anomaly data obtained from the values of the total magnetic field strenghthas been corrected. In this study, magnetic data acquisition was carried out in 97 points by using a PPM (Proton Precession Magnetometer) geometrics 856X. Data Processing began with International Geomagnetic Reference Field (IGRF) correction and diurnal correction to get the total magnetic anomaly. The total magnetic anomaly contour created by using Surfer that has been used to process upward continuation and then made reduction to the poles. The result of research showed the total magnetic anomaly closure pair of positive and negative indicated a fault zone below the surface. Mag2D used to create 2D modelling to obtain the subsurface structure and susceptibility values. To reinforce the results of subsurface structure, 3- modelling has been created by used Mag3D. In 2D-modelling of subsurface structure is obtained in the form of fault zones in the west an the east of the River Progo. The interpretation is reinforced by the result of 3D-modelling in the area. There are tworeserve faults in Progo River estuary area, first in the west of the Progo River and second in east Progo River to a depth of 1000 meters.